Postoperative follow‐up of Cushing's disease using cortisol, desmopressin and coupled dexamethasone‐desmopressin tests: a head‐to‐head comparison. (20th March 2015) - Le Marc'hadour, Pauline; Muller, Marie; Albarel, Frederique; Coulon, Anne‐Laure; Morange, Isabelle; Martinie, Monique; Gay, Emmanuel; Graillon, Thomas; Dufour, Henri; Conte‐Devolx, Bernard; Chabre, Olivier; Brue, Thierry; et al.
Summary Objective Predicting the outcome of patients operated on for Cushing's disease (CD) is a challenging task. Our objective was to assess the accuracy of immediate postsurgical plasma cortisol, desmopressin test and the coupled dexamethasone‐desmopressin test (CDDT) as predictors of outcome. Design and patients Sixty‐seven patients with initial remission and a minimal postsurgical follow‐up greater than 18 months were included in this retrospective bicentre study. Measurements Follow‐up included 3–6 months followed by yearly 24‐h urinary‐free cortisol, ACTH and cortisol plasmatic levels, a 1‐mg overnight dexamethasone suppression test (1‐mg DST), desmopressin test and the CDDT. ROC curves were performed to define the optimal threshold of immediate postsurgical cortisol level and 3‐ to 6‐month desmopressin test and CDDT, as predictors of final outcome in comparison with classical biological markers of recurrence. Results Eleven patients presented recurrence. The patient's median follow‐up was 52 months (range, 18–180). As early predictors of outcome, immediate postsurgical plasma cortisol level <35 nmol/l predicted the lack of recurrence with 93% negative predictive value (NPV), whereas predictive positive value (PPV) was 25%. During the follow‐up, the CDDT was more precise than the desmopressin test in predicting the lack of recurrence (100% NPV) when performed in the first 3 years after surgery. Positivity of the CDDT was defined based on ROC curves by ACTH and cortisol increments >50%. The CDDT was highly reproducible, as the same response was observed every year in 91% of the patients. Conclusions Adding the CDDT the first 3 years after surgery to immediate postsurgical cortisol evaluation should allow obtaining an optimal follow‐up management of patients operated for Cushing's disease.